Pro-environmental Behavior of Environmental Activists on the Slopes of Merapi - Putri, Yayan Eka; Triyono, Triyono (JSSH (Jurnal Sains Sosial dan Humaniora), 2025)
Environmental damage due to the eruption of Mount Merapi is a major threat to the people living around it. Various efforts must be made to reduce the impact of damage and improve environmental conditions. Balerante Village, located in Kemalang District, Klaten Regency, Central Java, is one of the areas experiencing the impact because of its proximity to Mount Merapi. Pro-environmental behavior should be crucial for environmental activists to implement in order to maintain environmental sustainability. This study aims to describe the pro-environmental behavior of environmental activists on the slopes of Merapi. The study used a qualitative phenomenological method with observation and interviews as data collection techniques, and the Interpretative Phenomenological Analysis (IPA) technique as a data analysis method. The results of the study showed that the behavior of environmental activists collaborated with advocacy, ecotourism, local culture, and reforestation that supported the reduction of natural resource exploitation. If environmental conservation is carried out consistently, the psychological condition of the community will experience various positive impacts, both individually and collectively.